Combined three monopoles for GPS/WLAN/GSM/WCDMA/LTE application. Issue 23 (1st November 2013) - Jeong, S.; Ren, Y.‐J.; Warden, J.; Lee, C.S.
Abstract : A novel compact antenna is designed on a low‐loss ceramic material to support multiband operation as well as to reduce the antenna size. Three monopole antennas with a single feed are designed and combined for wireless device applications, occupying only 10 × 10 × 3 mm 3 . Structurally, orthogonal placement of the three monopoles provides a relatively simple design process. Across the entire bands of interest, it is shown that more than 50% of the incident energy radiates into free space. Detailed analysis and measurement results are presented.